Avaliação dos efeitos do fator estimulante de colônias de granulócitos (g-csf) sobre os parâmetros estruturais e funcionais do ventrículo esquerdo de ratos submetidos à cardiomiopatia induzida pelo isoproterenol - Forechi, Ludimila (2011)
Background: The massive sympathetic discharge occurring in situations of severe stress or use of high doses of stimulants of the central adrenergic system has acute and chronic deleterious effects to the heart because multiple points of focal necrosis may occur on the endocardium with the consequent ventricular remodeling. Injections of high isoproterenol (ISO) doses have been used as an experimental model of this cardiomyopathy. Aim: To evaluate the effects of the Granulocytecolony stimulating factor (G-CSF) in this experimental model in rats. Methods: Male Wistar rats (N=155; 260-300g) were divided into three groups and used in different protocols: Controls (n=41), without any intervention, ISO (n=65) receiving ISO (150mg/kg/day, sc) for two consecutive days, and ISO+G-CSF (n=49) receiving the same dose of ISO and being treated with G-CSF (50µg/kg/day sc) for 7 days, beginning 24 hours after the last dose of ISO. Blood samples were taken from the saphenous vein to check leukocyte mobilization during the protocol. Echocardiography (7.5 MHz) was performed at the beginning and at the end of the protocol. At the 30th day after ISO, the animals were anesthetized (ketamine - 90mg/kg + xylazine -10mg/kg, ip) for arterial and left ventricle hemodynamic records. The heart was then arrested (KCl 3M) and a double lumen catheter was inserted into the LV cavity to obtain the left ventricular pressure x volume curve in the heart in situ. Fragments of left ventricle were prepared to histological analysis (Syrius red) to determine the fractional volumetric density of collagen. Data were analyzed by one and two-way ANOVA as appropriate, and the results expressed as mean ± standard error of mean. The statistical significance was set at p<0,05. Results: Mortality determined by ISO treatment of was 18.4%. The leukocyte count at the 3th day was higher in the ISO (20,393±1,534 céls./mm3 ) and in the ISO+G-CSF (18,987±1,541) groups than in the Control group (14,572±0,888). This difference was undetected at the 30th day of the protocol. There was no significant difference in the functional analysis of the heart in hemodynamic and echocardiograph measurements, as well as in relation to the body weight and viscera weights (heart, lungs and liver). ISO shifted to the right the pressure-volume curve (CT K1=2,70±0,32; ISO K1=2,37±0,24; ISO+G-CSF K1=2,69±0,36) and increased the diameter of the left ventricle at the end-diastole in the echocardiogram (CT 7,7±0,14; ISO 8,7±0,16; ISO+G-CSF 7,8±0,09 mm) characterizing the ventricular dilation in the ISO group, which was 7 prevented by G-CSF treatment. The left ventricular endocardial fractional collagen volume increased markedly in the ISO groups and it was partially reduced (p<0.05) by G-CSF (CT 2,0±0,18; ISO 9,1±0,81; ISO+G-CSF 5,9±0,58%). Conclusion: Treatment with G-CSF for 7 days was effective to prevent the onset of dilated cardiomyopathy produced by ISO in rats, with decreased collagen deposition in the extracellular matrix. This finding may be due to attenuation of lesions or to the reduction of the local inflammatory reaction produced by ISO treatment